2014
DOI: 10.1371/journal.pntd.0003392
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiles of the Protoscoleces of Echinococcus granulosus Reveal that Excretory-Secretory Products Are Essential to Metabolic Adaptation

Abstract: BackgroundCystic hydatid disease (CHD) is caused by the larval stages of the cestode and affects humans and domestic animals worldwide. Protoscoleces (PSCs) are one component of the larval stages that can interact with both definitive and intermediate hosts. Previous genomic and transcriptomic data have provided an overall snapshot of the genomics of the growth and development of this parasite. However, our understanding of how PSCs subvert the immune response of hosts and maintains metabolic adaptation remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 101 publications
0
29
0
Order By: Relevance
“…These results suggested that EgPSC-ESPs might induce a mixted pro-inflammatory and anti-inflammatory response in B cells, thereby maintaining immunity homeostasis. This seems to be expected, because the ESPs contained diverse components that perform different biological functions [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that EgPSC-ESPs might induce a mixted pro-inflammatory and anti-inflammatory response in B cells, thereby maintaining immunity homeostasis. This seems to be expected, because the ESPs contained diverse components that perform different biological functions [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…As previously described by Cucher et al [ 15 ], both species are the most frequent in human echinococcosis cases and are sympatric in many countries worldwide. At present, there are only two methods for the treatment of hydatid disease: surgery and the use of benzimidazole, but both have often unsatisfactory results [ 54 ]. Hence, novel treatment compounds are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Protozoan parasites similarly secrete a range of immunomodulatory molecules; for example, Trypanosoma cruzi mucins have been associated with suppression of active T cell immune responses by inducing arrest in the cell cycle [10] . Secreted parasite proteins have also been proposed to be involved in metabolic adaptation to the host environment [11] and tissue invasion, where proteases play a major role [12] . In the past 5 years, EVs have been revealed as another component of parasite secretion products that provide a previously unrecognized mechanism to package and protect a set of parasite cargo for uptake and integration into other cells.…”
Section: Host–parasite Interactions: Do We Know It All?mentioning
confidence: 99%